ASPECTS OF THE INFRINGEMENT IN THE RELIGIOUS EXPOSURE - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. Social sciences view a person as a qualitative characteristic of a person, which is formed in the process of activity and communication in a certain social environment. Representatives of humanistic philosophy pointed out that personality is a person as a value for which society is developing. In the conceptual plan, the work of the leading Ukrainian philosophers, sociologists, psychologists, such as V. Andrushchenko, I. Boychenko, L. Gubersky, V. Yevtukha, S. Krymsky, I. Manokhi, V. Moskalets, I. Nadolny , V. Roments, V. Chuika, V. Yaroshovtsa and others. P.Haidenko devoted his studies to the philosophical and theological views of S.Kercegor. For our intelligence, the ideas of S.Isaev were devoted to the problem of death in Protestant modernism. The researcher O. Stavtseva considered aspects of the concept of "existence", inherent in the philosophy of S. Kierkegaard, M. Heidegger F. Schelling. The relevance of the study is to analyze the crisis state of religious consciousness, to identify the content of the negative mental state (anxiety, despair, etc.) and overcome the ontological fear inherent in man. The aim and tasks is to identify how the problem of ontology of a person is solved through the phenomenon of fear, as it is connected with the general-methodological settings of existential philosophy, the heuristic potential of which is contained in this decision. On the basis of a comparative analysis of the metaphysical understanding of personality, we explore aspects of the phenomenon of fear and the possibilities of overcoming it. Research methods: Our study uses a set of methods. The system-structural method has allowed to consider each element of philosophical discourse in projection on the whole. The hermeneutic method was used to understand and interpret the philosophical texts of S. Kierkegaard, L. Shestov, P. Florensky, M. Berdyayev, and others like that. The symbolic-existential analysis method was used to interpret symbols. The cognitive approach provided a look at the philosophical discourse through the prism of processes of thinking, perception and understanding. Important were the methods of conceptual-comparative analysis and retrospective modeling, which allow to analyze semantic invariants and to compare the outlook models of texts, the subject of discourse. Discussion. The object of our study is the phenomenon of metaphysical fear in the religious existence. It is an archaic sense, and its dimensions at each level of civilizational development. Explorer.Caste wrote that the analysis of the specified sense, is crucial for understanding human behavior. S. Kara-Murza noted that the mass of religious existential fear is a characteristic feature of Western civilization. In our study we tried to analyze the concept of "german angst" (a strong sense that combines "depth", "deep", "death"). To reach the level of confidence in the future, security, peace of mind is possible with the help of the ideas proposed by the representatives of religious-philosophical cosmism N. Berdyaev and.P.Florensky, and the like. Specified and built the novelty of the research. Conclusions. If the ideas of Theophanes Sammitnik correlate with the positions of existential analyst M. Haydeger, then one can come to the conclusion that the fear of God is perfect and makes man a being capable of recreating the spiritual universe. S. Kercegor stressed that human existence is characterized by a deep rooted fear of death, before Nothing. The man who is the bearer of the fear of God has an ontological answer to the meaning of his life, overcoming the state of sin, even at the level of intentions, aspirations, and meanings. She becomes the bearer of qualitative endless transformations of moral, religious, and psychological quality. The consequence of this is the conscious existence, the realization of the existential purpose, and at the level of the soul - the state of indescribable bliss, that is, the satisfaction of life, a sense of pleasure and joy. So we find a certain similarity in the views of P. Florensky and M. Berdyayev on the problem of liberation from the feeling of fear of imminent death. The philosophers believed that this would happen in the spirit of human life throughout life. The phenomenon of death, in the work of M. Berdyayev, received a dual sense as an evil associated with the horror of physical extinction and as a blessing that inspires man to realize the consequences of his actions, to the redemption, to the expectation of "eternal life"; through the acceptance of the fear of God. The concurrence of the maxims of Berdyayev and the Christian Church, in the person of, for example, Ignatius Bryanchaninov, Theophanes Samitnik, p.P.Florensky, etc., is observed. The philosopher in the doctrine of death, as a blessing, added the idea of the possibility of redeeming sins and realizing the true meaning of being, due to being on the deathbed. M. Berdyayev actualized the causes of the horror before his death: the observation of the death of other people, the lack of understanding of how it acts on the physical body and soul, the grief for the dead, and contemplated the topic of hellish torture. The eschatological theme in the works of M.Berdyayev, O.P.Florensky made it possible to form an important notion of overcoming a man of fear, horror, anguish, through spiritual preparation for death throughout his life.